Surgery for the diabetic foot: A key component of care. (10th December 2019) - Frykberg, Robert G.; Wukich, Dane K.; Kavarthapu, Venu; Zgonis, Thomas; Dalla Paola, Luca; ,
Abstract: Surgery for acute and chronic diabetic foot problems has long been an integral component of care. While partial foot amputations remain as important diabetic limb‐salvaging operations, foot‐sparing reconstructive procedures have become equally important strategies to preserve the functional anatomy of the foot while addressing infection, chronic deformities, and ulcerations. A classification of types of diabetic foot surgery is discussed in accordance with the soft tissue status and acuity of the presenting foot problem. This brief overview from the Association for Diabetic Foot Surgeons describes common conditions best treated by surgical interventions, as well as specific indications. While techniques and indications continue to evolve, effective surgical management of the diabetic foot remains an integral component of care as well as for the prevention of recurrent ulceration.